Effect of epidural spinal cord stimulation on female sexual function after spinal cord injury - Shackleton, Claire; Samejima, Soshi; Miller, Tiev; Sachdeva, Rahul; Parr, Ann; Samadani, Uzma; Netoff, Theoden; Hocaloski, Shea; Elliott, Stacy; Walter, Matthias; Darrow, David; Krassioukov, Andrei (Frontiers in Neuroscience, 2023)
Sexual dysfunction is a common consequence for women with spinal cord injury (SCI); however, current treatments are ineffective, especially in the under-prioritized population of women with SCI. This case-series, a secondary analysis of the Epidural Stimulation After Neurologic Damage (E-STAND) clinical trial aimed to investigate the effect of epidural spinal cord stimulation (ESCS) on sexual function and distress in women with SCI. Three females, with chronic, thoracic, sensorimotor complete SCI received daily (24 h/day) tonic ESCS for 13 months. Questionnaires, including the Female Sexual Function Index (FSFI) and Female Sexual Distress Scale (FSDS) were collected monthly. There was a 3.2-point (13.2%) mean increase in total FSFI from baseline (24.5 ± 4.1) to post-intervention (27.8 ± 6.6), with a 4.8–50% improvement in the sub-domains of desire, arousal, orgasm and satisfaction. Sexual distress was reduced by 55%, with a mean decrease of 12 points (55.4%) from baseline (21.7 ± 17.2) to post-intervention (9.7 ± 10.8). There was a clinically meaningful change of 14 points in the International Standards for Neurological Classification of Spinal Cord Injury total sensory score from baseline (102 ± 10.5) to post-intervention (116 ± 17.4), without aggravating dyspareunia. ESCS is a promising treatment for sexual dysfunction and distress in women with severe SCI. Developing therapeutic interventions for sexual function is one of the most meaningful recovery targets for people with SCI. Additional large-scale investigations are needed to understand the long-term safety and feasibility of ESCS as a viable therapy for sexual dysfunction. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/NCT03026816, NCT03026816.